Detailed NMR, Including 1,1-ADEQUATE, and Anticancer Studies of Compounds from the Echinoderm Colobometra perspinosa - Catherine H. Liptrot; Philip S. Kearns; Cherie A. Motti; Simon P. B. Ovenden; Dianne M. Tapiolas; Anthony D. Wright; Jonathan L. Nielson (Marine Drugs, 2009)
From the dichloromethane/methanol extract of the crinoid Colobometra perspinosa, collected south east of Richards Island (Bedara), Family Islands, Central Great Barrier Reef, Australia, 3-(1'-hydroxypropyl)-1,6,8-trihydroxy-9,10-anthraquinone [one of the two stereoisomers of rhodoptilometrin, (1)], 3-propyl-1,6,8-trihydroxy-9,10-anthraquinone (3), 2-[(phenylacetyl)amino]ethanesulfonic acid (4), and 4-hydroxybutanoic acid (5) were isolated. Comparison of 1H- and 13C-NMR data for rhodoptilometrin (1) with those reported in the literature showed significant differences for some resonances associated with rings A and C. In an attempt to provide accurately assigned 1H- and 13C-NMR data, as well as to confirm the structure of 1, a thorough NMR investigation of this compound was undertaken. Measurements included: concentration dependent 13C, 1D selective NOE, HSQC, HMBC and 1,1-ADEQUATE. The NMR data for 4 and 5 are reported here for the first time, as is their occurrence from the marine environment. The in vitro anticancer activity of the original extract was found to be associated with 1, 3 and 5.